Preparation and tabletting of dipyridamole alginate-Eudragit microspheres - (:unkn) unknown (TAYLOR & FRANCIS LTD, 1998)
Dipyridamole alginate-Eudragit microspheres were prepared by the emulsification technique of Monshipouri and Price. After modification of the formulation and process variables of this method it was possible to obtain spherical and discrete particles. Microspheres were free flowing and the release of drug was slow compared to granules and powder. To further control the release rate of the drug, tablets of microspheres were prepared, adding 20% HPMC 90 SH 4000 and 90 SH 100 000 and compressing at 98 mPa or 147 mPa. Increasing the amount of additive and the compression pressure decreased the release rate of drug.
Keywords: dipyridamole; microencapsulation; alginate; Eudragit; tabletted microspheres; POLYMER DISPERSIONS; BEADS; DELIVERY; RELEASE